KONSEP BELAJAR DAN PEMBELAJARAN STUDI KOMPERASI PEMIKIRAN AL-GHAZALI DAN Al-ZARNUJI. - Indah Rizky Aulia; Khusnul Wardan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Abstrak ditulis maks Learning, as an effort to seek knowledge and learning, in the Islamic perspective can also be understood as a path to pursue knowledge. This is because learning is an obligation and a necessity. The concept of learning and learning in Islamic thought was put forward by figures who provided insights into the concept of learning, namely Al-Ghazali and Al-Zarnuji. Both share similarities in discussing ethics in the process of learning or seeking knowledge. Their well-known works include: Ihya’ Ulum al-Dinexplains the importance of knowledge, morals, and manners in the learning process. Meanwhile, Al-Zarnuji, through his work Ta‘lim al-Muta‘allim, emphasizing the learning procedures, manners, and practical strategies that a student must follow. This research uses the library research type.(library research), with literature in the form of books, articles and research results from previous studies. The type of library research is the study of the thoughts of figures. In the view of Al-Ghazali and Al-Zarnuji, it is explained that in the learning process it is necessary to prioritize the purity of the soul (purify the heart from bad behavior and reprehensible traits) with the intention of achieving Allah's pleasure, then carry out learning with istiqomah and earnestly and not being arrogant